PERBEDAAN KEMAMPUAN PUKULAN SERVIS PICKLEBALL ANTARA ATLET PEMULA DAN ATLET MENENGAH - Ifa Hamda Yauma Istikomah; Moch Fahmi Abdul Aziz (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
This study aims to determine the difference in pickleball serve skills between beginner and intermediate athletes. This study uses a comparative quantitative method with an independent two-group comparison design between beginner and intermediate athletes. The population in this study consisted of all 18 members of the Semarang State University Pickleball Club, comprising 8 beginner athletes and 10 intermediate athletes, selected using purposive sampling. Data collection used a structured service ability test that measured accuracy and consistency through ten service attempts. Data analysis was performed using descriptive statistics, normality tests, and independent two-sample t-tests. The results showed that intermediate athletes had higher average accuracy and consistency scores than beginner athletes. Statistical tests showed a significant difference between the two groups. These results indicate that training experience and playing intensity contribute to improved pickleball serving skills.